2009
DOI: 10.1002/glia.20942
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of astroglial connexin43 silencing uncovers a cytoskeletal platform involved in process formation and migration

Abstract: Connexin43 (Cx43) is the most abundant gap junction protein of the brain, where it is predominantly expressed in astrocytes. Recent studies imply a role of Cx43 in the regulation of important cellular processes, including migration, proliferation, and shape formation. These processes are assumed to be reflected by the proteome of the Cx43 expressing cells. To analyze the influence of Cx43 on the astrocytic proteome, we used RNA interference to downregulate the expression of this connexin in cultures of mouse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 62 publications
3
31
0
2
Order By: Relevance
“…This conclusion is supported by many studies that have demonstrated the critical role of Cx43 expressed by glioma cells in enhancing cell migration by increasing intercellular adhesion through the extracellular loop 33,34,38,39,90 and/or by interacting with the cytoskeletal signaling molecules, including F-actin, N-cadherin and cortactin via the cytoplasmic tail. 43,88 Reactive astrocytes express pro-inflammatory chemokines 8,10,110 that confer a survival advantage to tumor cells. In this regard, microglia have a major part in cytokine-mediated pathways in glioma progression.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by many studies that have demonstrated the critical role of Cx43 expressed by glioma cells in enhancing cell migration by increasing intercellular adhesion through the extracellular loop 33,34,38,39,90 and/or by interacting with the cytoskeletal signaling molecules, including F-actin, N-cadherin and cortactin via the cytoplasmic tail. 43,88 Reactive astrocytes express pro-inflammatory chemokines 8,10,110 that confer a survival advantage to tumor cells. In this regard, microglia have a major part in cytokine-mediated pathways in glioma progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that Cx43 modulated cytoskeletal proteins including MAPRE1, which are involved in process formation and migration of astrocytes. Besides, Stephan et al found that MAPRE1 expression depended on the level of Cx43 expression by the method of immunocytochemistry and western blot [42]. In the present study, we showed that there was no difference in protein and gene expression of MAPRE1 after IR/OGDR at time points 0.5, 1, 3, 6, 12, 24, and 72 h. In agreement with this viewpoint, we also found that the total number of Cx43 was unchanged in the normal and IR/OGDR groups.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of actin-stabilizing proteins such as cofilin and transgelin, in our proteomic analysis, is also altered. Binding of cofilin and transgelin to actin stabilizes actin–tubulin complex and therefore regulates cellular process formation and cell migration [39]. Changes in cytoskeletal proteins as a result of CCM dysregulation can further disturb the cell–cell interaction as seen in several dysregulation in cell junction signal (Figure 5A–E).…”
Section: Discussionmentioning
confidence: 99%